The effect of individual and classroom moral disengagement on antisocial behaviors in Colombian adolescents: A multilevel model - Gomez Plata, Maryluz; Laghi, Fiorenzo; Pastorelli, Concetta; Paba Barbosa, Carmelina; Uribe Tirado, Liliana; Luengo Kanacri, Bernadette P.; Zuffiano, Antonio; Cirimele, Flavia; Ruiz García, Marcela; Tamayo Giraldo, Gonzalo; Narváez Marín, Mariela; Gerbino, Maria G. (Frontiers in Education, 2022)
The present study examined the predictive effect of moral disengagement (within and between classrooms) on antisocial behaviors in Colombian adolescents, as well as the interaction of moral disengagement with classroom composition by age, socioeconomic status (SES), and perceived teacher–student relationship quality. Multilevel modeling was used to identify individual, compositional, and contextual effects on antisocial behaviors. The predictive variables were: (a) classroom mean score (i.e., between-classroom analysis), and (b) student deviation from the classroom mean score (i.e., within-classroom analysis). The sample included 879 students nested in 24 seventh-grade classrooms in three Colombian cities. The results showed that age, SES, and moral disengagement at the within-classroom level predicted antisocial behaviors. At the between-classroom level, antisocial behaviors were predicted by higher moral disengagement and lower aggregate SES. In addition, significant interactions were found between moral disengagement at the within-classroom level and SES at the between-classroom level. The findings expand our knowledge of the interdependence between individual and classroom contexts in the exercise of moral agency during adolescence.